Characteristics of Biodegradable Polylactide/Thermoplastic Starch/Nanosilica Composites: Effects of Plasticizer and Nanosilica Functionality - Regina Jeziorska; Agnieszka Szadkowska; Ewa Spasowka; Aneta Lukomska; Michal Chmielarek (Advances in Materials Science and Engineering)
The effect of plasticizer (polydimethylsiloxanol) and neat (SiO2) or modified (having amine functional groups) silica (A-SiO2) on morphology, thermal, mechanical, and rheological properties of PLA/TPS blends compatibilized by maleated PLA (MPLA) was investigated. Toughened PLA/MPLA/TPS (60/10/30) blend containing 3 wt.% of plasticizer and various contents (1, 3, or 5 wt.%) of silica were prepared in a corotating twin-screw extruder. From SEM, it is clear that plasticized PLA/MPLA/TPS blend continuous porous structure is highly related to the silica content and its functionality. The results indicate that polydimethylsiloxanol enhances ductility and the initial thermal stability of the plasticized blend. DSC and DMTA analyses show that nucleation ability and reinforcing effect of A-SiO2 on plasticized blend crystallization are much better than those of SiO2. Silica practically had no effect on the thermo-oxidative degradation. However, the composites with A-SiO2 had better thermal stability than those with SiO2. Moreover, silica significantly improved the elongation at break.